Wh-Questions in Translation among Arab EFL Learners: Challenges and Solutions - Al-Hassaani, Abdulbari Mahboob Ahmed (Journal of Ecohumanism, 2024)
This study focused on using of English Wh-question sentences translation into Arabic and vice versa by the Yemeni EFL learners, second year level, English Department, College of Education and Sciences, Saber-Lahj, University of Lahj, Yemen. The number who participated in this study were thirty-five learners, fifteen boys and twenty girls. This study used one academic instrument for collecting data and information (a quantitative method), that was students’ questionnaire including the translation test on English Wh-question sentences translation and Arabic Wh-question sentences translation which distributed randomly in their English classes. The major problem of the Yemeni EFL learners was the lack of understanding the accurate grammar rules in constructing English W-h questions and they faced challenges and difficulties when they translate the English W-h questions into Arabic and vice versa. The difference in the usage of the English Wh-question sentences and the Arabic Wh-question sentences (Asmaa Al-Istifham) was the main cause of the interference. Arab learners have difficulties of first language (L1) interference. The main aim of this study was to identify the challenges and difficulties of the Yemeni EFL learners encounter in translating the English Wh-question sentences into Arabic and the Arabic Wh-question sentences into English. In conclusion the researcher can say that most of the Yemeni EFL learners of second year level, English Department, College of Education and Sciences at University of Lahj made mistakes in translating the English Wh-question sentences into Arabic and vice versa, because of their week background in English and they practice translation only during the class time which was not enough for mastering the grammar rules of English Wh-questions construction. Besides, most of the learners started to study English from class seven at late ages and stages. This affected negatively on their performance in translation the English Wh-question sentences into Arabic and the Arabic W-h questions; what is called in Arabic (Istifham Al-Taswur) into English.